182k views
5 votes
Is my answer correct?

Is my answer correct?-example-1
User Rindress
by
4.9k points

2 Answers

6 votes

Answer:

No, we do not multiply the first equation by 2 and then add it to the second equation. We have to multiply the first equation by 4.

To illustrate this point, consider system A:

If we multiply the first equation by 2, we get

Now, if we replace the second equation with the sum of the second equation and , we get

which simplifies to

This is not an equivalent system to System B. We can see that we ended up with a 2y = 4 equation.

In order to end up with a 2x = 10 second equation, we have to multiply the first equation of system A by 4 to get

If we replace the second equation with the sum of the second equation and , we get

which simplifies to

Otherwise, you are correct. The solution to system B is the solution to system A. Adding an equation to another doesn't change the system

Explanation:

User Lapsio
by
5.4k points
5 votes

No, we do not multiply the first equation by 2 and then add it to the second equation. We have to multiply the first equation by 4.

To illustrate this point, consider system A:


\left\{ \begin{aligned}x - y &= 3 \\-2x + 4y &= -2\end{aligned}\right.

If we multiply the first equation by 2, we get


2x - 2y = 6

Now, if we replace the second equation with the sum of the second equation and
2x - 2y = 6, we get


\left\{ \begin{aligned}x - y &= 3 \\(-2x+2x) + (4y - 2y) &= -2 + 6\end{aligned}\right.

which simplifies to


\left\{ \begin{aligned}x - y &= 3 \\2y &= 4\end{aligned}\right.

This is not an equivalent system to System B. We can see that we ended up with a 2y = 4 equation.

In order to end up with a 2x = 10 second equation, we have to multiply the first equation of system A by 4 to get


4x - 4y = 12

If we replace the second equation with the sum of the second equation and
4x - 4y = 12, we get


\left\{ \begin{aligned}x - y &= 3 \\(-2x+4x) + (4y-4y) &= -2 + 12\end{aligned}\right.

which simplifies to


\left\{ \begin{aligned}x - y &= 3 \\2x &= 10\end{aligned}\right.

Otherwise, you are correct. The solution to system B is the solution to system A. Adding an equation to another does not change the system.

User Ayal Gelles
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.